Association of birth outcomes and postnatal growth with adult leukocyte telomere length: Data from New Delhi Birth Cohort. Issue 4 (17th July 2019) - Tarik, Mohamad; Ramakrishnan, Lakshmy; Sinha, Sikha; Sachdev, Harsh Pal Singh; Tandon, Nikhil; Roy, Ambuj; Bhargava, Santosh Kumar
Abstract: Born small for gestational age due to undernutrition in utero and subsequent catch‐up growth is associated with risk of developing chronic diseases in adulthood. Telomere length has been shown to be a predictor of these age‐related diseases and may be a link between birth size, a surrogate for foetal undernutrition, and adult chronic diseases. We assessed the relationship of leukocyte telomere length in adult life with birth outcomes and serial change in body mass index (BMI) from birth to adulthood. Leukocyte relative telomere length (RTL) was measured by MMqPCR in 1, 309 subjects from New Delhi Birth Cohort who participated in two phases of the study between 2006–2009 (Phase 6) and 2012–2015 (Phase 7) at a mean age of 39.08 (±3.29), and its association with birth outcomes and conditional BMI gain at 2, 11, and 29 years was assessed in a mixed regression model. We did not find any significant association of RTL with body size at birth including birthweight, birth length, and birth BMI. Gestational age was positively associated with RTL ( P  = .017, multivariate model: P  = .039). Conditional BMI gain at 2 and 11 years was not associated with RTL. BMI gain at 29 year was negatively associated with RTL in multivariate model ( P  = .015). Born small for gestational age was not associated with RTL in adulthood. Leukocyte telomere attrition was observed in those born before 37 weeks of gestational age as well as in those who gained weight as adults, which may predispose to chronic diseases.